Issues in the preservation of manually tanned skin materials - Torunn Klokkernes (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The field of conservation relates to material science and technology as a fundamental aspect to understand artefacts’ material properties and deterioration. The research performed in this study is an initial approach to the understanding of the complex nature of manually tanned skin materials manufactured by individual tradition bearers from indigenous cultures in the circumpolar area; it instigates a series of research topics which can be further addressed. Contextual interpretation comprises traditional knowledge and practices as well as the empirical information obtained through investigative and analytical methods. This requires collaboration between several areas of knowledge, and raises questions with regard to the interpretation of analytical results in the investigation of these material groups.